Efektivitas Praktek Pengalaman Lapangan Program Studi Pendidikan Bahasa Arab Terhadap Kompetensi Mengajar Mahasiswa / The Effectiveness of Field Experience Practice in Arabic Language Education Study Program on Students' Teaching Competence - Irfan Irfan; Wahab Wahab; Eva Gusmira; Abdul Qoyyim (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2025)
This study aims to determine the effectiveness of field experience practice on students' pedagogical, personality, social and professional competencies. Effectiveness is assessed from the perception of supervising teachers. The research sample was taken using the purposive random sampling technique, namely schools that have arabic language supervising teachers from 38 schools. The research method uses mixed method research with a sequential strategy of the explanatory type. Data collection techniques using questionnaires, interviews and documentation. The content validity test was carried out by three experts and the construct validity test. The reliability test used SEM-PLS version 3.0. The data analysis technique used was the mixed method technique. Quantitative analysis used the mean formula which was continued with qualitative analysis. The results of the study found that students' pedagogical and social competencies were high and had very high personality and professional competencies. The results of the interview found several shortcomings in students' pedagogical competencies, namely in making lesson plans, and making computer-based learning media. The shortcomings in social competence are unequal relationships with teachers and the school environment. This is the basis for development for program managers to be able to improve student competency before PPL students.Abstract: Penelitian ini bertujuan untuk menentukan efektivitas praktek pengalaman lapangan terhadap kompetensi pedagogik, kepribadian, sosial dan profesional mahasiswa. Efektivitas dinilai dari penilaian guru pamong. Sampel penelitian diambil menggunakan teknik Purposive Random Sampling yaitu sekolah yang memiliki guru pamong bahasa arab dari 38 sekolah. Metode penelitian menggunakan Mixed Method Research dengan strategi sequential tipe Explanatory. Teknik pengumpulan data dengan teknik angket, wawancara dan dokumentasi. Uji validitas isi dilakukan oleh tiga orang ahli dan uji validitas konstruk. Uji reliabilitas menggunakan SEM-PLS versi 3.0. Teknik analisis data yang digunakan adalah teknik mixed method. Analisa kuantitatif menggunakan rumus mean yang dilanjutkan dengan analisa kualitatif. Hasil penelitian menemukan kompetensi pedagogik dan kompetensi sosial mahasiswa tinggi serta memiliki kompetensi kepribadian dan kompetensi profesional yang sangat tinggi. Hasil wawancara menemukan beberapa kekurangan dalam kompetensi pedagogik mahasiswa yaitu dalam pembuatan RPP, dan pembuatan media pembelajaran berbasis komputer. Kekurangan dalam kompetensi sosial adalah pergaulan yang kurang merata dengan guru, dan lingkungan sekolah. Hal ini menjadi dasar pengembangan bagi pengelola program agar dapat meningkatkan kompetensi mahasiswa sebelum mahasiswa PPL.